DISCURSIVE CONSTRUCTION OF POWER IN STUDENTS’ ANONYMOUS FEEDBACK - Ha, Nguyen Thi Thu; Giang, Nguyen Huong; Huyen, Vu Minh (VNU Journal of Foreign Studies; Vol 33 No 3, 2017)
This study was conducted on more than 400 negative anonymous comments, in which students convey some complaint or express discontent about their teachers. The study takes a poststructruralist approach to discourse analysis, positioning that power is contructed and negotiated through discourse (Foucault, 1972; Fairclough, 2010; Mills, 1997). The study aims to find out how students actually do their power through linguistic choices by looking at some pragmatic aspects such as speech acts, addressing terms and politeness strategies (Yule, 1996). The study found that students explicitly do power in this discourse; besides, negotiation of traditional roles was also present. This reflects the complexity of the teachers – students power relation in a comtemporary Vietnam, in which there exist both market economy’s definition of education and traditional perception of teaching and learning.